Early versus delayed repair of vesicouterine fistula - Bettez, Mathieu (Canadian Medical Association, 2011)
Vesicouterine fistulas (VUF) are a pathological and uncommon connection between the uterus and the bladder. Although rare, they are usually related to cesarean section. Nowadays, their incidence increases because of the increase in Cesarean sections. Patients with VUF may have various clinical presentations. The main symptoms are urinary incontinence, which may be associated with hematuria. Vesicouterine fistulas are usually associated with psychological distress and have a negative effect on quality of life. The accurate and early diagnosis of VUF can be difficult. There are multiple ways to investigate VUF and several examinations may be required to confirm the diagnosis; these examinations may include a cystoscopy, a retrograde cystography, methylene blue test and a computed tomography scan. We present 3 cases of vesicouterine fistula with successful surgical repair in which 2 patients had an early repair. One patient had an early surgical repair because of intractable pain and the other patient because of the large size of the fistula. The fistula repair surgeries were uneventful and the patients had an unremarkable recovery. We report that early surgical management is technically feasible without significantly increasing the difficulty of the surgery, with an excellent outcome in selected patients.